Mediation of coffee-induced improvements in human vascular function by chlorogenic acids and its metabolites: Two randomized, controlled, crossover intervention trials. Issue 6 (December 2017) - Mills, Charlotte E.; Flury, Andreas; Marmet, Cynthia; Poquet, Laura; Rimoldi, Stefano F.; Sartori, Claudio; Rexhaj, Emrush; Brenner, Roman; Allemann, Yves; Zimmermann, Diane; Gibson, Glenn R.; Mottram, Don S.; et al.
Summary: Background & aims: Polyphenol intake has been linked to improvements in human vascular function, although data on hydroxycinnamates, such as chlorogenic acid (CGA) have not yet been studied. We aimed to investigate the impact of coffee intake rich in chlorogenic acid on human vascular function and whether CGAs are involved in potential effects. Methods: Two acute randomized, controlled, cross-over human intervention trials were conducted. The impact of coffee intake, matched for caffeine but differing in CGA content (89, and 310 mg) on flow-mediated dilatation (FMD) was assessed in 15 healthy male subjects. In a second intervention trial conducted with 24 healthy male subjects, the impact of pure 5-caffeoylquinic acid (5-CQA), the main CGA in coffee (5-CQA; 450 mg and 900 mg) on FMD was also investigated. Results: We observed a bi-phasic FMD response after low and high polyphenol, (89 mg and 310 mg CGA) intake, with increases at 1 (1.10 ± 0.43% and 1.34 ± 0.62%, respectively) and 5 (0.79% ± 0.32 and 1.52% ± 0.40, respectively) hours post coffee consumption. FMD responses to coffee intake was closely paralleled by the appearance of CGA metabolites in plasma, notably 3-, 4- and 5-feruloylquinic acid and ferulic-4′-O-sulfate at 1 h and isoferulic-3′-O-glucuronide and ferulic-4′-O-sulfate at 5 h. Intervention with purified 5-CQA (450 mg) also led to an improvement in FMD response relative to control (0.75 ± 1.31% at 1 h post intervention, p = 0.06) and concomitant appearance of plasma metabolites. Conclusions: Coffee intake acutely improves human vascular function, an effect, in part, mediated by 5-CQA and its physiological metabolites. Study registration: The National Institutes of Health (NIH) on ClinicalTrials.gov NCT01813981 and NCT01772784 . Highlights: Coffee is a rich source of phenolic acids, called chlorogenic acids, a subclass of (poly)phenols. Coffee induces biphasic improvements in endothelial function. Change in endothelial function correlates with plasma chlorogenic acid metabolites.